Advanced Analyses of Text - Mohamed, Emad Jasem (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study aims to analyze texts through analysis of invisible text, which includes many meanings, expressions and norms that can be accessed by symbolic behavior such as language, literature, and the arts. In recent decades, the rapid increase in the development and availability of resources and computational technology has led to an increase in the analysis of multimedia texts that appear in a range of disciplines in clouded in the above study the prevalence of contemporary digital media forms requires researchers to keep sociocultural developments. At this stage, multimedia studies are required as a kind of experimental text